The Effect of Gymnastics: Aerobic Low Impact on Reducing Blood Pressure in Hypertensive Elderly - Marni Marni; Masyita Mamot; Zelia Maria Da Silva; Mursudarinah Mursudarinah (Indonesian Journal of Global Health Research, 2023)
Hypertension is a non-communicable disease but is a major health problem in the world and is the third largest cause of premature death because its prevalence continues to increase. Prevention of hypertension that can be done is doing aerobic exercise, limiting salt intake. increase your intake of fruits, vegetables, and nuts, a healthy diet, a healthy lifestyle. to determine the Effect of Gymnastics: Aerobic Low Impact on blood pressure in elderly hypertensives in Cemani Village. Quasi-experimental research design (Ramadhani & Santik, 2021) with a pre-test-post test without a control group . The research instrument in this study was a respondent characteristic questionnaire containing gender, age, education and occupation. Sphygmomanometer tension Omron digital and stethoscope. Speakers and MP3s that have music as accompaniment during the intervention, SOPs that are used to explain the steps for Aerobic Low Impact exercises and observation sheets that contain notes on the results of blood pressure measurements before and after the intervention activities and observation sheets that list the participants' attendance. Data analysis in this study was univariate analysis in the form of frequency and percentage distributions and bivariate analysis using the Willcoxon Signed ranks test . The results showed a significant decrease in blood pressure after being given low impact aerobic exercise with an average of 145.79/88.14 mmHg decreased to 128.93/80.79 mmHg. is an effect of Aerobic Low Impact exercise on reducing blood pressure in the elderly.